Management of stage III non-small-cell lung cancer: rays of hope - Floryane Kim; Maxime Borgeaud; Alfredo Addeo; Alex Friedlaender (Open Exploration Publishing Inc., 2024)
Lung cancer remains the most common cause of cancer death across the world. Non-small-cell lung cancer (NSCLC) represents the most frequent type of lung cancer and is frequently diagnosed at an advanced stage. Stage III NSCLC, which encompasses 30% of cases, refers to a state between localized and metastatic disease, and is associated with poor prognosis. As highlighted in this review, stage III represents a heterogenous group, whose complex management includes multimodal treatment, discussed below, and requires discussion in multidisciplinary teams. The goal of this approach is a maximalist attitude in these patients with locally advanced and non-metastatic disease. However, many issues remain under debate including the optimal sequences of treatment between different treatment modalities, patient selection particularly for surgery, the duration of perioperative treatments and the identification of biomarkers to determine which patients might benefit of specific treatment like immunotherapy and targeted therapies. This review describes the current landscape of management of stage III NSCLC, discussing the critical issue of resectability, and highlighting the recent advancements in the field, particularly the incorporation of immune-checkpoint inhibitors (ICIs) and targeted therapies in this setting.